Efficacy of deferoxamine in animal models of intracerebral hemorrhage: a systematic review and stratified meta-analysis. - Han-Jin Cui; Hao-yu He; A-Li Yang; Hua-Jun Zhou; Cong Wang; Jie-Kun Luo; Yuan Lin; Tao Tang (PLoS ONE)
Intracerebral hemorrhage (ICH) is a subtype of stroke associated with high morbidity and mortality rates. No proven treatments are available for this condition. Iron-mediated free radical injury is associated with secondary damage following ICH. Deferoxamine (DFX), a ferric-iron chelator, is a candidate drug for the treatment of ICH. We performed a systematic review of studies involving the administration of DFX following ICH. In total, 20 studies were identified that described the efficacy of DFX in animal models of ICH and assessed changes in the brain water content, neurobehavioral score, or both. DFX reduced the brain water content by 85.7% in animal models of ICH (-0.86, 95% CI: -.48- -0.23; P < 0.01; 23 comparisons), and improved the neurobehavioral score by -1.08 (95% CI: -1.23- -0.92; P < 0.01; 62 comparisons). DFX was most efficacious when administered 2-4 h after ICH at a dose of 10-50 mg/kg depending on species, and this beneficial effect remained for up to 24 h postinjury. The efficacy was higher with phenobarbital anesthesia, intramuscular injection, and lysed erythrocyte infusion, and in Fischer 344 rats or aged animals. Overall, although DFX was found to be effective in experimental ICH, additional confirmation is needed due to possible publication bias, poor study quality, and the limited number of studies conducting clinical trials.